MODERN COSTUME DESIGN BASED ON THE ASSOCIATIVE TRANSFORMATIONS OF THE FOLK CLOTHES TECTONIC STRUCTURES - Ніколаєва, Т. В.; Гайова, І. Л.; Ніколаєва, Т. І.; Гладка, В. А. (Art and Design, 2020)
Improving the design process of modern clothes and determining the sign-symbolic functions of costume, inspired by ethnic motives, by studying methods of the associative transformation of the folk costume tectonic structure based on the use of various types of structural transformations. System-informational, visual-analytical research methods are used in the work. Systematic and structural analyses of the artistic and compositional elements transformations in the shaping of a modern costume based on associative conversion is applied.Results. Based on the investigation, the interconnection between associative signs and structural building of modern women’s clothes, designed upon a folk costume construction basis, has been determined. The research of the most expressive elements of traditional clothes has been carried out with the purpose to determine symbolic functionality of a contemporary costume. Principles of project implementation of associative structural transformations of costume forms, spatial elements layout and order of their placement using different types of tectonic transformation have been determined, and classification of structural transformations has been developed. Scientific novelty lies in the development of modern costume designing methods based on the forms and structure of traditional folk clothes. This makes it possible to determine the variability of the use of relationships of morphological and associative transformations of the object and improving the design processes of new promising costume forms. The results of scientific work can be used in the practical activity of costume designers in order to develop promising collections of modern clothes for contests and exhibitions.The results allow to optimize the design process of modern clothing models.